The Effect of Digital Literacy, Innovative Attitudes, and Interpersonal Communication on Teacher Performance - Wasis Dewanto; Encep Syarifudin; Sholeh Hidayat; Suryadi Suryadi (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2024)
Objective: Assessing a teacher's performance may involve examining how much they have achieved the necessary competencies. This research investigates the effect of digital literacy, innovative attitudes, and interpersonal communication on teacher performance. Method: The statistical survey methodology was employed in this study in order to substantiate its findings. The researchers of this study employed the Partial Least Squares-Structural Equation Model (PLS-SEM) to derive the latent variable values. This investigation was conducted at a public elementary school in Serang City, in the Banten Province of Indonesia. The Serang City region in Indonesia is home to 14 public primary schools. The study sample comprised 14 school administrators and 236 public elementary school teachers in Serang City, Banten, Indonesia. The sampling technique was random sampling. The questionnaire functions as the instrument for gathering data in this study. Results: The research uncovered four noteworthy and statistically significant discoveries. One is that a direct relationship exists between digital literacy and innovative mindsets. A direct relationship exists between innovative mindsets and teacher performance. A direct relationship exists between digital literacy and interpersonal communication. Interpersonal communication and teacher performance exhibit a positive association. Novelty: This research is intriguing due to variations in emphasis, research participants, and incorporation of research factors compared to earlier studies. Previous research only examined digital literacy, innovative attitudes, interpersonal communication, and teacher performance. This research will combine digital literacy, innovative attitudes, interpersonal communication, and teacher performance into a single research topic.